Local Politics, Organized Interests, and Land-Use Policy: A Research Note Analyzing the Perceptions of Urban Planners Working in City Government. (November 2014) - Heberlig, Eric; Leland, Suzanne; Read, Dustin
This research note examines the influence of organized interests in the land-use policy-making process from the perspective of urban planners employed in city government. Perceptions of these professionals are evaluated using a series of regression models controlling for the mitigating effects of government structure, mayoral partisanship, community characteristics, and the personal attributes of the respondents participating in the research. The results suggest that the aggregate influence of organized interests is more pronounced in cities with mayors when compared with cities with council–manager government structures. Furthermore, there is some evidence that the presence of a partisan mayor can increase the aggregate influence of organized interests, as well as mitigate the amount of influence garnered by specific groups. These findings contribute to the study of urban development by offering new insight into the relationship between local politics, organized interests, and land-use policy.